Adaptabilidade e avaliação de progênies de Acca sellowiana (O. Berg) Burret oriundas de melhoramento genético participativo no sul do Brasil - Sohne, Ana Elisia (2022)
The feijoa is a native species of Southern Brazil and Northeast of Uruguay, with commercial crops and genetic improvement well structured in international scope, specially at New Zealand and Colombia. It has a high potential for cultivation compared to other fruit trees widely cultivated in Brazil. However, despite being well studied, the genetic improvement in Brazil has not yet produced varieties adapted to the different soil and climatic conditions of its area of natural occurrence. The present study aims to evaluate the performance and growth adaptation of seven progenies obtained from crosses between A. sellowiana matrices from a participatory breeding program in eight different locations in southern Brazil, characterizing these segregating populations by identifying superior progenies with better adaptation to the conditions of each place evaluated in relation to the characteristics of survival and initial growth, identifying preferential and marginal places of cultivation for the crossings and plants. The quality of fruits of some progenies in Vacaria - RS was also analyzed in order to highlight promising progenies. The plants were evaluated at 2.5 and 7 years of age, and the height from the ground to the top of the crown (cm), the crown diameter (cm) and the sectional area of the plant neck (mm²) were measured for growth analysis. The data was transformed into annual growth rates to equalize the analyses, in addition to the plant mortality rate at the sites. For the analysis of Vacaria fruits, the fruit diameter (cm), length (cm), total weight (g), pulp yield (%), peel thickness (mm), soluble solids content (°Brix) and total titratable acidity (% citric acid) was measured. It was concluded that there was a GxE interaction for plant growth and mortality. There was better adaptation in general to the Caçador, Ipê, Maquiné and Paraí locations. Dois Vizinhos, David Canabarro, Rio do Sul and Vacaria had lower performance. Likewise, the 1001xHel and 1006xHel plants with greater survival stood out. On the other hand, plants of 1004x1035 and 1051x1035, despite greater growth, had low survival. Therefore, from these results it is not possible to identify an ideal location or progeny, as studies with the fruits are also necessary for the selection of plants in each location, as this is the purpose of their cultivation. Regarding the fruits of Vacaria, the fruits generated by plants three (455) and nine (1001) stand out as promising plants in size, pulp yield and SS content of the fruits, but more studies are needed for an effective selection, as these were the first crops analyzed.